The Globular Amphora Culture on the territory of Western Palessye: history if research and current state of studies - Vaitovich, Aliaksandra U. (Journal of the Belarusian State University. History, 2020)
In the history of the archaeological research of the Globular Amphora Culture on the territory of Western Palessye, two periods are distinguished. U. F. Isayenka was the first who pointed out the presence of Globular Amphora Culture elements on the SouthWestern region of Belarus in the second half of the 1960s. In the 1960–90s the issue of the Globular Amphora Culture on the area of interest to us appeared on the margins of studies of other cultures. The works had been based on the cultural bricks theory. Since the end of the 1990s the polythetic notion of the Globular Amphora Culture had been suggested (M. Szmyt). The special study on the Globular Amphora Culture on the territory of Western Palessye had begun (M. M. Kryvaltsevich, A. U. Vaitovich (Zuyeva)). The publications consider mostly aspects of the systematization and identification of the traits genetically linked to the Globular Amphora Culture in the local cultural environment. On the current stage of research, the expansion of the source database is needed. The issue of the chronology of the spreading of the Globular Amphora Culture traditions in the area in question requires more detailed study. Top priority should also be given to a thorough investigation of the problem of the role of the Globular Amphora Culture in the socioeconomic transformation of the Western Palessye population in the 3rd – the beginning 2nd millenium BC.
Keywords: historiography; Globular Amphora Culture; cultural identification; Western Palessye; Neolithic; Bronze Age